Clinical and epidemiological aspects of leukemias - Almeida, Anne Louise Soares; Azevedo, Isabelle Campos de; Carvalho, Diana Paula de Souza Rego Pinto; Vitor, Allyne Fortes; Santos, Viviane Euzébia Pereira; Ferreira Júnior, Marcos Antonio (Revista Cubana de Hematología, Inmunología y Hemoterapia, 2017)
Leukemia is a group of clonal diseases derived from a single cell with a genetic alteration in bone marrow or peripheral lymphoid tissue, and each type is determined by the specificity of the source cell. The objective of this research was to synthesize studies that characterize the clinical and epidemiological profile of patients with leukemia, the types of treatments used, duration and outcomes for the cases. This study is an integrative review of literature through databases Medical Literature Analysis and Retrieval System Online (MEDLINE), SCOPUS, Cumulative Index to Nursing & Allied Health Literature (CINAHL) and Science Direct. There were 4,274 articles rescued in the initial search, 188 were selected to compose the review sample after applying all the criteria for inclusion and exclusion adopted. Full articles were grouped into four categories, according to the variables of research: (a) more frequent subtypes of leukemia; (B) most widely used treatment; (C) duration of treatment; and (d) endpoint of the cases. It is concluded a prevalence of leukemia in pediatric patients, with a predominance of the subtype Acute Lymphoblastic Leukemia (ALL). In general, the male population is more affected by hematological malignancies. As the therapy is used, each leukemia subtype had its peculiarities regarding the treatment, especially the introduction of imatinib for chronic myeloid leukemia (CML) and prophylactic cranial irradiation for cases of ALL. Chronic leukemia showed higher treatment duration. There was a significant improvement in survival of Acute Myeloid Leukemia, Chronic Lymphoblastic leukemia, CML and ALL, approximately with 90% cure rate in children.